ANALYSIS OF THE EURASIAN ECONOMIC INTEGRATION: A MULTIDIMENSIONAL PERSPECTIVE - Orazbay Lazzat (European Research Materials, 2023)
The Eurasian Economic Union (EAEU) has achieved certain milestones while also confronting various challenges. Drawing upon regional integration theory, this paper delineates the EAEU along the dimension of economic integration, providing a comprehensive and systematic analysis of the organization. In the economic integration dimension, the EAEU is positioned between a customs union and a common market, facing difficulties in further deepening its integration. The EAEU also treads a fine line between national and supranational dynamics, essentially adhering to a consensual decision-making model, lacking institutional innovation. Within the integration dimension, member states exhibit diverse stances on Eurasianism, emphasizing geopolitical and geo-economic objectives, thereby fracturing identity construction and impeding collective action. The lack of a harmonious interplay among these three dimensions of regional integration significantly influences the EAEU's future development.